2016
DOI: 10.7754/clin.lab.2016.160212
|View full text |Cite
|
Sign up to set email alerts
|

Albuminuria is Suggested as a Potential Health Screening Biomarker for Senior Citizens and General Population with Hypertension or Diabetes in China

Abstract: Albuminuria should be suggested as a potential health screening biomarker in senior citizens and general population with hypertension and diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The clinical test with the highest sensitivity and the best predictive value for an early diagnosis of DN is the measurement of albuminuria in urinary tests; measuring MAL is considered the ‘gold standard’. Although, clinically, MAL is used for an early diagnosis of DN, it is affected by a variety of factors, such as systemic or urinary tract infections, bleeding, vigorous exercise, or kidney damage related to drugs. Therefore, MAL alone cannot provide a timely and accurately diagnosis DN.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical test with the highest sensitivity and the best predictive value for an early diagnosis of DN is the measurement of albuminuria in urinary tests; measuring MAL is considered the ‘gold standard’. Although, clinically, MAL is used for an early diagnosis of DN, it is affected by a variety of factors, such as systemic or urinary tract infections, bleeding, vigorous exercise, or kidney damage related to drugs. Therefore, MAL alone cannot provide a timely and accurately diagnosis DN.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have used this information to identify associations between outcomes. One study reported that albuminuria may be a biomarker for hypertension and diabetes mellitus;8 another study reported serum uric acid to be positively associated with pulmonary function 9. Moreover, lifestyle factors have been shown to be associated with gastroesophageal reflux disease, and one study linked health screening and claims data to predict hospitalization due to pneumonia 1011.…”
mentioning
confidence: 99%